Congenital esophageal stenosis associated with esophageal atresia. Issue 3 (1st April 2015) - McCann, F.; Michaud, L.; Aspirot, A.; Levesque, D.; Gottrand, F.; Faure, C.
Summary: Congenital esophageal stenosis (CES) is a rare clinical condition but is frequently associated with esophageal atresia (EA). The aim of this study is to report the diagnosis, management, and outcome of CES associated with EA. Medical charts of CES-EA patients from Lille University Hospital, Sainte-Justine Hospital, and Montreal Children's Hospital were retrospectively reviewed. Seventeen patients (13 boys) were included. The incidence of CES in patients with EA was 3.6%. Fifteen patients had a type C EA, one had a type A EA, and one had an isolated tracheoesophageal fistula. Seven patients had associated additional malformations. The mean age at diagnosis was 11.6 months. All but two patients had non-specific symptoms such as regurgitations or dysphagia. One CES was diagnosed at the time of surgical repair of EA. In 12 patients, CES was suspected based on abnormal barium swallow. In the remaining four, the diagnostic was confirmed by esophagoscopy. Eleven patients were treated by dilation only (1–3 dilations/patient). Six patients underwent surgery (resection and anastomosis) because of failure of attempted dilations (1–7 dilations/patient). Esophageal perforation was encountered in three patients (18%). Three patients had histologically proven tracheobronchial remnants. CES associated with EA is frequent. A high index of suspicion for CES must remain in the presence of EA. Dilatation may be effective to treat some of them, but perforation is frequent. Surgery may be required, especially in CES secondary to ectopic tracheobronchial remnants.